2019
DOI: 10.1038/s41598-019-56686-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and their targeted genes associated with phase changes of stem explants during tissue culture of tea plant

Abstract: Elucidation of the molecular mechanism related to the dedifferentiation and redifferentiation during tissue culture will be useful for optimizing regeneration system of tea plant. In this study, an integrated sRNAome and transcriptome analyses were carried out during phase changes of the stem explant culture. Among 198 miRNAs and 8001 predicted target genes, 178 differentially expressed miRNAs and 4264 potential targets were screened out from explants, primary calli, as well as regenerated roots and shoots. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…19 In tea plant, miR166a-3p was considered to be involved in the regulation of stem explant dedifferentiation and redifferentiation. 35 In our data, the expression levels of miR166c, miR166h, and miR166j were higher in bud than in lateral root, which may have the same function as previously reported for miR166a-3p. In the research about miRNAs related to the sprout development of tea plant cultivar "Pingyang Tezaocha", 21 related DEmiRNAs were found.…”
Section: ■ Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19 In tea plant, miR166a-3p was considered to be involved in the regulation of stem explant dedifferentiation and redifferentiation. 35 In our data, the expression levels of miR166c, miR166h, and miR166j were higher in bud than in lateral root, which may have the same function as previously reported for miR166a-3p. In the research about miRNAs related to the sprout development of tea plant cultivar "Pingyang Tezaocha", 21 related DEmiRNAs were found.…”
Section: ■ Discussionsupporting
confidence: 89%
“…In leaf development, miRNA166 was shown to regulate the polarity of maize leaf through hd-zipIII family member rolled leaf1 ( rld1 ) . In tea plant, miR166a-3p was considered to be involved in the regulation of stem explant dedifferentiation and redifferentiation . In our data, the expression levels of miR166c, miR166h, and miR166j were higher in bud than in lateral root, which may have the same function as previously reported for miR166a-3p.…”
Section: Discussionsupporting
confidence: 87%
“…Low expression levels of sly-miR166c-5p and sly-miR166c-3p were observed during the change from stem to callus stages in this study. Previous research has shown that miR166, together with miR156 and miR396 were down-regulated during callus formation from tea plant stem explants [ 73 ]. miR166 was identified to target Class III homeodomain leucine zipper (HD-Zip III) gene family of transcription factors, including REVOLUTA (REV), PHABULOSA (PHB), PHAVOLUTA (PHV), CORONA (CNA), and ATHB8 in Arabidopsis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…together with miR156 and miR396 were down-regulated during callus formation from tea plant stem explants [73]. miR166 was identified to target Class III homeodomain leucine zipper (HD-Zip III) gene family of transcription factors, including REVOLUTA (REV), PHABU-LOSA (PHB), PHAVOLUTA (PHV), CORONA (CNA), and ATHB8 in Arabidopsis [43].…”
Section: Plos Onementioning
confidence: 99%
“…Low expression levels of sly-miR166c-5p and sly-miR166c-3p were observed during the change from stem to callus stages in this study. Previous research has shown that miR166, together with miR156 and miR396 were down-regulated during callus formation from tea plant stem explants[77]. miR166 was identified to target Class III homeodomain leucine zipper (HD-Zip III) gene family of transcription factors, including REVOLUTA (REV), PHABULOSA (PHB), PHAVOLUTA (PHV), CORONA (CNA), and ATHB8 in Arabidopsis [49].…”
Section: Discussionmentioning
confidence: 99%